In-situ ultrasonic enhancement of flux during natural rubber skim latex recovery by ultrafiltration - Anitha S; Devaraj V; Zairossani M N (Journal of Rubber Research, 2008)
DL
Keywords: Cross-flow ultrafiltration; Membrane fouling; Skim latex; Transmembrane pressure; Ultrasonic